The use of digital educational resources in the support to learning in higher education - Morais, Carlos; Miranda, Luísa; Alves, Paulo (EAI Endorsed Transactions on e-Learning, 2015)
This paper aimed to assess the importance given to the use of digital educational resources, their use frequency, and their classification considering them as a support to course units. The data was obtained through questionnaire and provided by a sample of undergraduates. We reflected on the concept of digital educational resource and presented the results of a study assessing the importance given by undergraduates to digital educational resources as well as their classification as a support to learning concerning aspects associated with learning strategies, motivation and learning tasks. We used research methodologies associated with both the quantitative and the qualitative paradigms. The results showed the existence of significant differences, between the 1st and the 2nd year students regarding the item study alone. The characterization of digital educational resources was made based on the answers given to open-ended questions and their further classification.